PENANAMAN BUDAYA MEMBACA DONGENG MELALUI RUMAH PINTAR DI DESA MARMOYO - Prihatin, Yulianah (Jurnal Terapan Abdimas, 2020)
Abstract. The low interest in reading in Indonesia, requires educational institutions to create innovations to help increase public interest in reading. In 2011, based on data from the World’s Most Literate Nations, Indonesia ranked 60th in the population's interest in reading. The sequence is classified as low compared to other countries. Currently the government has made the National Literacy Movement as an effort to increase the percentage of people's interest in reading. But it needs to be supported by many parties. Based on this, the KKNT team in the village of Marmoyo made an innovation to establish a Smart House so that the community would be more fond of reading, especially reading stories to their children. Fairy tales are one form of folklore that develops both orally and in writing. Regions in Indonesia have thousands of fairy tales that are worth preserving, because the young generation knows and knows the developing tales. In addition, the activity of reading fairy tales to children (ndongeng) proved able to instill character and create closeness between parents and children. The method in this service is carried out by analyzing the situation of partners, reviewing literature / references related to the theme of PKM, conducting a fairytale reading training with an interesting method in Marmoyo village for two days, civilizing reading fairy tales through smart homes. The fairytale reading training program and the application of the Smart House in the village of Marmoyo proved to be able to change the mindset of the community about the benefits of fairy tales, as well as facilitate the community in finding reading material.Abstrak. Rendahnya minat baca di Indonesia, mengharuskan lembaga pendidikan menciptakan inovasi untuk membantu menaikkan minat baca masyarakat. Pada tahun 2011 berdasarkan data dari World’s Most Literate Nations, Indonesia berada pada urutan ke 60 tentang minat baca penduduknya. Urutan itu tergolong urutan yang rendah dibandingkan negara-negara yang lainnya. Saat ini pemerintah sudah membuat Gerakan Literasi Nasional sebagai bentuk upaya menaikkan persentase minat baca masyarakat. Namun hal itu perlu didukung oleh banyak pihak. Berdasarkan hal tersebut, tim KKNT di desa Marmoyo membuat inovasi untuk mendirikan Rumah Pintar agar masyarakat semakin gemar membac, terutama membacakan dongeng untuk anak-anaknya. Dongeng merupakan salah satu bentuk dari cerita rakyat yang berkembang baik secara lisan maupun tulis. Daerah di Indonesia memiliki ribuan dongeng yang patut untuk dilestarikan, hal tersebut dikarenakan agar generasi muda mengenal dan mengetahui dongeng yang berkembang. Selain itu, kegiatan membacakan dongeng pada anak (ndongeng) terbukti mampu menanamkan karakter dan menciptakan kedekatan antara orang tua dan anak. Metode pada pengabdian ini dilakukan dengan cara analisis situasi mitra, Pengkajian pustaka/referensi yang terkait dengan tema PKM, pelaksanaan Pelatihan membaca dongeng dengan metode yang menarik di desa Marmoyo selama dua hari, pembudayaan membaca dongeng melalui rumah pintar. Progam pelatihan membaca dongeng dan penerapan Rumah Pintar di desa Marmoyo terbukti mampu mengubah pola pikir masyarakat tentang manfaat dongeng, serta memudahkan masyarakat dalam mencari bahan bacaan.